2015
DOI: 10.1515/jpem-2014-0465
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism as a rare cofactor in chronic kidney disease (CKD) – related anemia

Abstract: The thyroid gland function should be assessed both in differential diagnostics of anemia and in case of unsatisfactory treatment with ESA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…84 The analysis of patients on dialysis revealed that thyroid dysfunction occurs significantly more often in patients in whom the hemoglobin concentration is lower than 12.5 mg/ dl. The most common type of thyroid abnormality is low T 3 syndrome defined as an abnormally low T 3 concentration, usually accompanied by normal TSH and free thyroxine concentrations, but not associated with primary thyroid disease.…”
Section: Autoimmune Hemolytic Anemia and Evans Syndromementioning
confidence: 99%
“…84 The analysis of patients on dialysis revealed that thyroid dysfunction occurs significantly more often in patients in whom the hemoglobin concentration is lower than 12.5 mg/ dl. The most common type of thyroid abnormality is low T 3 syndrome defined as an abnormally low T 3 concentration, usually accompanied by normal TSH and free thyroxine concentrations, but not associated with primary thyroid disease.…”
Section: Autoimmune Hemolytic Anemia and Evans Syndromementioning
confidence: 99%
“…Erythropoietin failed to correct her anaemia, and subclinical hypothyroidism was diagnosed and subsequently treated. Upon normalisation of thyroid function, haemoglobin levels increased and the clinical situation improved (8). Despite the fact that this report seems to be unique and potentially clinical improvement upon thyroid supplementation might be coincidental, it stresses the fact that thyroid function should be tested in patients with complex disorders at least once if there is any suspicion of hypothyroidism or any clinical signs suggestive of thyroid dysfunction.…”
Section: Hypothyroidismmentioning
confidence: 73%